2022
DOI: 10.1159/000521596
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy for Hepatocellular Carcinoma: Chinese Consensus-Based Interdisciplinary Expert Statements

Abstract: Background: Hepatocellular carcinoma (HCC) is the most common type of liver cancer and causes many cancer-related deaths worldwide; in China it is the second most prevalent cause of cancer deaths. Most patients are diagnosed clinically with advanced stage disease. Summary: For more than a decade, sorafenib, a small molecular weight tyrosine kinase-inhibitor (SMW TKI) was the only molecular targeted drug available with a survival benefit for the treatment of advanced HCC. With the development of novel TKIs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“… 14 Nowadays, there are two approved agents (Sorafenib and Lenvatinib) as the first-line options in China. 26 In this study, we analyzed 229 consecutive HCC patients with EHM undergoing treatment with TKI combined PD-1 inhibitor as Sora+PD-1 group (n = 127) and Len+PD-1 group (n = 102). We found that, compared with Sora+PD-1 treatment, Len+PD-1 treatment had significantly better OS and PFS in HCC patient with EHM.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Nowadays, there are two approved agents (Sorafenib and Lenvatinib) as the first-line options in China. 26 In this study, we analyzed 229 consecutive HCC patients with EHM undergoing treatment with TKI combined PD-1 inhibitor as Sora+PD-1 group (n = 127) and Len+PD-1 group (n = 102). We found that, compared with Sora+PD-1 treatment, Len+PD-1 treatment had significantly better OS and PFS in HCC patient with EHM.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine kinase inhibitor (TKI) sorafenib was approved by the USA FDA in 2007 for the treatment of advanced HCC. Increasing oral multi-targeted TKIs were subsequently awarded permission for use in treating HCC worldwide [31,32]. Furthermore, we evaluated the relationship between RM_Score and Sorafenib sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly because the early diagnosis of liver cancer is very difficult, leading to the majority of patients with liver cancer being diagnosed as an advanced stage. At present, the efficacy of traditional systemic chemotherapy is very low, and the side effects are great [ 3 , 4 ]. Moreover, the liver cancer recurrence rate following 5 recurrence-free years after liver cancer treatment is high [ 5 ].…”
Section: Introductionmentioning
confidence: 99%